Factors driving contractors to implement energy management strategies in construction projects. Issue 3 (5th November 2018) - Enshassi, Adnan; Ayash, Abed; Mohamed, Sherif
Abstract : Purpose: The purpose of this paper is to investigate the factors driving Palestinian construction contractors to implement energy management strategies during the execution of construction projects. Design/methodology/approach: The study was conducted by administering a questionnaire that comprised 26 drivers for adopting energy management strategies. Data were collected from 67 contractors in the Gaza Strip. Factor analysis was adopted to explore the underlying relationships among the identified drivers. Findings: Drivers were grouped into one of the four categories: economic and financial, institutional and legal, organisational and managerial and educational and informational. The results revealed that the majority of the respondents were of the view that economic and financial factors were the most important factors driving the adoption of energy management strategies by construction companies in the Gaza Strip. Of the economic and financial drivers, the cost savings derived from the adoption of energy management strategies was considered the most important item. Energy management education and training programmes are scarce in the Gaza Strip, and local contractors have no formal energy management education and training. The government needs to allocate sufficient funds for policy implementation and regulation enforcement. Research limitations/implications: Difficulties in accessing energy management data are deemed as a limitation to this study, as the topic of energy management in the construction has received no or very little academic attention so far. Practical implications: This study provides a valuable reference for studying ongoing research in the practice of energy management development in other industries and locations. The priority of the drivers for energy management will help the local contracting companies to focus on weak and strong points of the company for energy use development to remove these weak points and invest in strong points. This paper results can increase the encouragement for greater social responsibility of the contracting organisations towards energy use. Government and concerned organisations can get benefits from the identified factors in encouraging contractors to adopt energy management strategy in their projects. Originality/value: This study is the first investigation of energy management aspects in a local construction industry, especially from contracting organisations.